Influence of various nitrogen applications on protein and amino acid profiles of amaranth and quinoa - Sa Nguansak Thanapornpoonpong (2018)
The effect of nitrogen application levels (0.16 and 0.24 g N kg -1 soil) on seed proteins and their amino acid compositions of amaranth (Amaranthus spp.) and quinoa (Chenopodium quinoa Willd) was studied. Total proteins of amaranth and quinoa had high contents of lysine (6.3-8.2 g 100 g-1 protein) but low contents of methionine (1.2-1.8 g 100 g -1 protein). Seed proteins were fractionated on the basis of different solubility in water, saline, and buffer as albumin-1 (Albu-1), albumin-2 (Albu-2), globulin (Glob), and glutelin (Glu) and were identified by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Albu-1 was high in lysine (5.4-8.6 g 100 g-1 protein), while Albu-2, which is a part of storage proteins, had a high leucine content (7.2-8.9 g 100 g-1 protein) as an effect of different nitrogen application levels. Glu fractions were well-balanced in their essential amino acids with the exception of methionine. In conclusion, nitrogen application can be used for the nutritional improvement in human diet by increasing and maintaining protein and essential amino acid contents. © 2008 American Chemical Society.